Mismatched ambition, execution and outcomes: implementing maternal death surveillance and response system in Mtwara region, Tanzania. Issue 5 (21st May 2021) - Said, Ali; Sirili, Nathanael; Massawe, Siriel; Pembe, Andrea B; Hanson, Claudia; Malqvist, Mats
Abstract : Background: Since 2015, Tanzania has been implementing the Maternal Death Surveillance and Response (MDSR) system. The system employs interactions of health providers and managers to identify, notify and review maternal deaths and recommend strategies for preventing further deaths. We aimed to analyse perceptions and experiences of health providers and managers in implementing the MDSR system. Methods: An exploratory qualitative study was carried out with 30 purposively selected health providers and 30 health managers in four councils from the Mtwara region between June and July 2020. Key informant interviews and focus group discussions were used to collect data. Inductive thematic analysis was used to analyse data. Results: Two main themes emerged from this study: 'Accomplishing by ambitions' and 'A flawed system ' . The themes suggest that health providers and managers have a strong desire to make the MDSR system work by making deliberate efforts to implement it. They reported working hard to timely notify, review death and implement action plans from meetings. Health providers and managers reported that MDSR has produced changes in care provision such as behavioural changes towards maternal care, increased accountability and policy changes. The system was however flawed by lack of training, organisational problems, poor coordination with other reporting and quality improvements systems, assigning blame and lack of motivation. Conclusion: The implementation of the MDSR system in Tanzania faces systemic, contextual and individual challenges. However, our results indicate that health providers and managers are willing and committed to improve service delivery to avoid maternal deaths. Empowering health providers and managers by training and addressing the flaws will improve the system and quality of care.